A comparison of face-to-face and online training in improving managers' confidence to support the mental health of workers - Gayed,A; Tan,L; LaMontagne,AD; Milner,A; Deady,M; Milligan-Saville,JS; Madan,I; Calvo,RA; Christensen,H; Mykletun,A; Glozier,N; Harvey,SB (Internet Interventions, 2019)
BackgroundIn recognition of the important role managers play in the well-being of the staff they supervise, many workplaces are implementing specialised training for leaders to help them better understand and support the mental health needs of their staff. This training can be delivered through face-to-face or online training sessions. Evaluation of such programs have found positive results for each format when compared to a control group, but to date, face-to-face and online manager mental health training have not been compared with one another.AimsThis study brings together results from two trials evaluating the same program content, each employing a different mode of content delivery. Both types of training aimed to change managers' confidence to better support the mental health needs of the staff they supervise.MethodsUtilising data derived from two previously conducted trials, mean change in manager confidence from baseline at both post-intervention and follow-up were examined for each method of content delivery. An identical way of measuring confidence was used in each study.ResultsManagers' confidence improved from baseline with both methods of training. A greater change was observed with face-to-face training than for online, although both methods had sustained improvement over time. Analyses indicate that at follow-up, improvements in confidence were significant for both face-to-face (t18=5.99; P<.001) and online training (t39=3.85; P<.001). Analyses focused on managers who fully completed either type of training indicated very similar impacts for face-to-face and online training.ConclusionsBoth face-to-face and online delivery of manager mental health training can significantly improve managers’ confidence in supporting the mental health needs of their staff. This change is sustained over various follow-up periods. However, lower retention rates common in online training reduce the relative effect of this method of delivery.